10-Year Institutional Retrospective Case Series of WHO Grade II Gliomas and Correlation of Incidence of Seizures, Isocitrate Dehydrogenase No. 1 (IDH-1) Mutation and Lobar Location (2010-2020). (1st October 2022) - Lammy, Simon; Bridgman, Elsie; Johnson, Hannah; Taylor, Aaron; Grivas, Athanasios
Abstract: AIMS OBJECTIVES: To assess the correlation in World Health Organisation (WHO) Grade II gliomas of IDH-1 mutation, lobar location and seizures DESIGN: 10-year retrospective case series SUBJECTS: Histopathological WHO Grade II gliomas METHODS: We searched case notes in NHS Greater Glasgow & Clyde and Scottish National PACS. RESULTS: 84 patients underwent tissue diagnosis. Mean age 42rs (range: 21-77yrs]). Seizures (NB: pre-2017 International League against Epilepsy classification [ILAE]) occurred in 71% (52% generalised, 37% partial and 11% mixed). 31% had ongoing seizures postoperatively. 38% had headache (50% had headache and seizures). 21% had a focal neurological deficit (FND) (61% had a FND and seizure). Seizure, as an isolated pre-operative symptom occurred in 48% patients compared to isolated headache in 10% and isolated FND in 4%. Overall, 58% of lesions and 60% of seizures were frontal. Histologically, 60% were astrocytomas and 40% oligodendrogliomas (49% of astrocytomas and 71% of oligodendrogliomas arose from the frontal lobe). IDH-1 mutation occurred in 80% (75% had seizures) and 66% were frontal. CONCLUSION: This confirms a correlation between IDH-1, incidence of seizures and frontal lesions (p = <0.05) REFERENCES Zhong et al. IDH1/2 Mutation is Associated with Seizure as an Initial Symptom in Low-Grade Glioma. Epilepsy Res. 2015 109:100-105